Analisis Gaya Bahasa Cerpen Senyum Karyamin dan Jasa-jasa Buat Sanwirya Karya Ahmad Tohari serta Implikasinya dalam Pembelajaran Sastra di SMP - Kezia Konehe; Oldie S. Meruntu; Viktory N. J. Rotty (Pustaka Digital Indonesia, 2026)
Teaching short story analysis for junior high school students often does not prioritize the examination of writing style, which limits student understanding. Ahmad Tohari's writing uses a choice of writing style to express meaning, convey social criticism, and foster empathy. The purpose of this study is to analyze the language style contained in Ahmad Tohari's short stories, especially Smile Karyamin and Jasa-jasa Buat Sanwirya, and to explore its influence on the teaching of short stories in junior high school. This study uses a library study methodology. The research location is the library. The research time is from November 2025 to February 2026. The data source for this study is the Smile Karyamin Short Story Anthology by Ahmad Tohari. The data analysis technique follows the steps of the content analysis technique. The language style data analysis technique is based on Gorys Keraf's theory. The results of the study show that the short story